Tongan Volcanic Eruption Intensifies Tropical Cyclone Cody (2022) - Liu, Haiyang; Tang, Xiaodong (Frontiers in Earth Science, 2022)
The aerosol−cloud impacts of the Tongan volcanic eruptions on the nearby tropical cyclone (TC) Cody on 14~15 January 2022 are investigated by MODIS satellite and ERA5 reanalysis data. Both the precipitation and intensity of Cody were obviously enhanced after the main blast of Tongan volcanic eruption on January 15, although the sea surface temperature and vertical wind shear of environmental wind did not change much according to ERA5 data. The vision that a large amount of volcanic aerosol flowed from the Tongan eruption into the indraft of Cody was captured by the MODIS observations on January 15. The cloud top temperature dropped, and the cloud particle effective radius decreased in Cody from then on, which indicated the occurring of deep convection there. The analyzed results of ERA5 show that convection was strengthened in the periphery of Cody at the beginning of the volcanic eruption on 03:00 UTC January 15 and later in Cody’s inner core after the main blast on 06:00 UTC January 15. This could be because of the microphysical process of aerosol−cloud interaction, which inhibited stratiform precipitation, increased vertical velocity, and enhanced convective precipitation further. Since the deep convection in the inner core was conducive to the development of Cody, the total precipitation and intensity of Cody both increased after the main blast of the volcanic eruption. The result also suggests that major volcanic eruptions could increase the convective intensity and induce heavy precipitation in a nearby organized convective system (e.g., TC or mesoscale convective systems).